The mystery of the ureteric stent in the lumen of the terminal ileum - Jimie, Joachim (BMJ Case Rep, 2020)
A 65-year-old comorbid female patient presented to our urology department with a history of multiple interventions to treat severe overactive bladder symptoms. She had a history of clam ileocystoplasty, which was then converted to an ileal conduit due to failure to resolve her symptoms. She subsequently developed multiple complications, most significantly ureteroileal stenosis, managed with bilateral ureteric stents. She later decided on bilateral nephrostomies and subsequent antegrade stent insertion. At follow-up, the proximal end of the left stent remained within the kidney and the distal end was free within the abdominal cavity. There was further migration of the stent in its entirety into the lumen of the terminal ileum on subsequent imaging. She denied any significant gastrointestinal symptoms, signs or peritonitis. Consideration was made for the endoscopic removal of the stent by the gastrointestinal team; however, the patient refused any further procedures preferring to be monitored.